Description of three new species and one new genus in American Acanthocinini (Coleoptera, Cerambycidae) - Santos-Silva, Antonio; Monné, Miguel A. (Zootaxa, 2023)
Three new species of Acanthocinini are described: Pseudosparna swifti sp. nov., from Costa Rica; Pseudosparna paulista sp. nov., from Brazil; and Xenocona chulumani sp. nov., from Bolivia. A new genus of Acanthocinini is described to include Pseudolepturges caesius Monné & Monné, 2007, and it is included in a previous key.